The correlation of knowledge and attitude on clean and healthy living practices in junior high school adolescents: A cross-sectional study - Wiwiet Susan Amelia; Toto Harto (Lentera Perawat, 2025)
Background: Clean and Healthy Living Practices (PHBS) are essential for preventing communicable diseases among adolescents, yet many junior high school students continue to demonstrate inconsistent hygiene behaviors despite exposure to school-based health programs. Objective: This study aimed to examine the correlation between knowledge and attitude with PHBS behaviors among adolescents in a junior high school setting. Methods: A cross-sectional design was employed, involving 39 students selected through total sampling. Data were collected using structured questionnaires measuring knowledge, attitude, and PHBS behaviors. Descriptive statistics were used to present frequency distributions, while Chi-Square tests examined the relationship between variables. Results: Most adolescents demonstrated poor knowledge (48.7%) and moderate attitudes toward PHBS. PHBS behaviors were mostly in the fair (46.2%) and poor (48.7%) categories. Cross-tabulation showed that adolescents with good or very good knowledge did not necessarily demonstrate better PHBS behaviors. Statistical analysis indicated no significant correlation between knowledge and PHBS (p = 0.74). Attitude also showed no significant association with PHBS. Conclusion: Knowledge and attitude were not significantly related to PHBS behavior among adolescents, suggesting that cognitive and affective factors alone are insufficient to shape consistent hygiene practices. Multi-level interventions involving schools, families, and communities are needed to strengthen adolescent PHBS behaviors.